Brand awareness as predictors of repurchase intention: Brand attitude as a moderator - Razak, Nurlaely; Themba, Orfyanny Syahreffy; Sjahruddin, Herman (Advances in Social Sciences Research Journal, 2019)
This study empirically investigates the moderating effect of brand attitude on the relationship between brand awareness and repurchases intention. The study proposes that the brand attitude acts as a quasi-moderator of the relationship between brand awareness and repurchase intention. The results support the predictions of the study. The results indicate that brand attitude moderates the relationship between brand awareness and repurchase intention such that when brand attitude is high, the relationship between brand awareness and repurchase intention is positive, and vice versa, when the brand attitude is low, the relationship between brand awareness and repurchase intention is negative. Furthermore, the results reveal that brand awareness and brand attitude has a positive relationship to repurchase intention. In other exploration results, found consumer-specific characteristics affect brand awareness. Consumer characteristics (e.g., ages, gender, and frequency of consumption (in times per month)) are not significantly and positively related to brand awareness, furthermore consumer characteristics is significantly and positively related to brand attitude